A Bis(silylenyl)pyridine Zero‐Valent Germanium Complex and Its Remarkable Reactivity. (2nd November 2016) - Zhou, Yu‐Peng; Karni, Miriam; Yao, Shenglai; Apeloig, Yitzhak; Driess, Matthias
Abstract: The synthesis, reactivity, and electronic structure of the unique germylone iron carbonyl complex[SiNSi]Ge 0 →Fe(CO)4 is reported. The compound was obtained in 49 % yield from the reaction of the bis(N‐heterocyclic silylenyl)pyridine pincer ligandSiNSi (1, 6‐C5 NH3 ‐[EtNSi(N t Bu)2 CPh]2 ) with GeCl2 ⋅(dioxane) to give the corresponding chlorogermyliumylidene chloride precursor[SiNSi]Ge II Cl + Cl −, which was further reduced with K2 Fe(CO)4 . Single‐crystal X‐ray diffraction analysis of[SiNSi]Ge →Fe(CO)4 revealed that the Ge 0 center adopts a trigonal‐pyramidal geometry with a Si‐Ge‐Si angle of 95.66(2)°. Remarkably, one of the Si II donor atoms in the complex is five‐coordinated because of additional (pyridine)N→Si coordination. Unexpectedly, the reaction of[SiNSi]Ge →Fe(CO)4 with GeCl2 ⋅(dioxane) (one molar equivalent) yielded the first push–pull germylone–germylene donor–acceptor complex, [SiNSi]Ge →GeCl2 →Fe(CO)4 through the insertion of GeCl2 into the dative Ge 0 →Fe bond. The electronic features of the new compounds were investigated by DFT calculations.